WORK READINESS IN FINAL STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS MALIKUSSALEH UNIVERSITY - Yanita; M Raihan Al Mubarak; Nurmala; Hamdiah (RADJA PUBLIKA, 2023)
Work readiness is one of the attributes that new graduates need to have. Work readiness is the condition when new graduates feel ready and ready to be successful in the work environment. In Indonesia, until now studies explaining the measurement of work readiness itself are still limited. This research aims to develop work readiness for undergraduates so that it can be useful both for companies, universities and the graduates themselves. The success of an institution, organization or company is supported by the success of the workforce at work, and the success of the workforce at work is the result of the work readiness that the workforce has. Work Readiness or job readiness is really needed by every individual before entering the world of work. Therefore, students, especially final students, must have good work readiness. Work Readiness must be carefully prepared while students are going through the study process so that when they graduate, students will have complete work readiness to enter the world of work. Work Readiness influences three variables, namely academic achievement, career development, and career self-efficacy. This research aims to determine the work readiness of final students at the Faculty of Economics & Business, Malikussaleh University. This research uses primary data using research instruments in the form of questionnaires with a sample of 100 respondents with a population of 503 students. The results of this research show that research instrument testing, for Validity, rcount > rtable (0.196) and Reliability, Cronchbach Aplha > Constant (0.60). The data analysis method used is multiple linear regression analysis and hypothesis testing in the form of t-test (partial). The results of the research partially show that Academic Performance, Career Development and Career Self-Efficacy have a positive and significant influence on Work Readiness in Final Students of the Faculty of Economics & Business, Malikussaleh University.